ijee 2022
DOI: 10.48165/ijee.2022.58321
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Conservation Agriculture in terms of Knowledge, Perception and Application

Abstract: Depleting natural resources, environmental pollution and climate change are the three major factors of concern simmering up with contemporary global agriculture. Conservation agriculture (CA) is being flagged up as a sustainable adaptation mechanism. Adoption of CA depends upon ecological as well as, farmers’ level of perception, knowledge acquisition, and decision-making process. The present study was taken place in West Bengal covering both the new alluvial zone (NAZ) and terai zones (TZ) following snowballi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The ultimate goal of this scale was to probe the relationship between farmer perception and the effect it has on farmer adoption behaviour towards sustainable practises in RWCS. The farmers' perception and adoption behaviour are positively correlated as seen in the studies of Mottaleb (2018); Chatterjee et al, (2022); Choudhary et al, (2022) & Vecchio et al, (2022. During the exhaustive search for the appropriate research problem, it was found that little effort had been made in the study of farmers' perceptions of the sustainability of RWCS in particular.…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate goal of this scale was to probe the relationship between farmer perception and the effect it has on farmer adoption behaviour towards sustainable practises in RWCS. The farmers' perception and adoption behaviour are positively correlated as seen in the studies of Mottaleb (2018); Chatterjee et al, (2022); Choudhary et al, (2022) & Vecchio et al, (2022. During the exhaustive search for the appropriate research problem, it was found that little effort had been made in the study of farmers' perceptions of the sustainability of RWCS in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, there is a rising concerns on how to feed the growing population with depleting resources and shrinking food production system. Chatterjee et al, (2022) reported a massive loss of agricultural output in the Indian market which was poised to affect market equilibrium of demand and supply. The problem is significant for India as it supports 18 and 37 per cent of global human and livestock population from meagre 2.4 per cent of global land and four per cent of global freshwater resources.…”
Section: Introductionmentioning
confidence: 99%